Shen-Kang protects against tacrolimus-induced renal injury - Long Ye Zhang; Jian Jin; Kang Luo; Shang Guo Piao; Hai Lan Zheng; Ji Zhe Jin; Sun Woo Lim; Bum Soon Choi; Chul Woo Yang; Can Li (The Korean Journal of Internal Medicine, 2019)
Background/Aims Evidence suggests that Shen-Kang (SK), a traditional Chinese herbal medicine, protects against various types of renal injury. In this study, we evaluated whether SK treatment confers renoprotection in a rat model of chronic tacrolimus (TAC) nephropathy. Methods Rats were treated daily with TAC (1.5mg/kg, subcutaneously) and SK (450 mg/kg, intravenously) for 4 weeks. The effects of SK on TAC-induced renal injury were assessed by measuring renal function, urine albumin excretion, histopathology, inflammatory cell infiltration, expression of profibrotic (transforming growth factor β1 [TGF-β1] and TGF-β inducible gene-h3 [βig-h3]) and proinflammatory cytokines, oxidative stress, and apoptotic cell death. Results Administration of SK preserved glomerular integrity (fractional mesangial area and Wilms tumor 1-positive glomeruli), attenuated tubulointerstitial fibrosis, and reduced the number of ectodermal dysplasia 1-positive cells, and this was paralleled by improved urine albumin excretion and renal dysfunction. At the molecular level, SK treatment suppressed expression of TGF-β1/Smad2/3, βig-h3, and proinflammatory cytokines. Oxidative stress and apoptotic cell death were significantly decreased with SK treatment, and apoptosis-related genes were regulated toward cell survival (active caspase-3 and the B-cell lymphoma-2/Bcl2-associated X [Bcl-2/Bax] ratio). Conclusions SK protects against TAC-induced renal injury.